Recurrence Factors in Cervical Precancerous Lesions: A Narrative Exploration - Fitriyadi Kusuma; Geraldus Sigap Gung Binathara; Kemal Akbar Suryoadji; Tsaniya Meidini Tahsya Hermawan; Vira Nur Arifa; Marshaly Safira Masrie (Griya Widya: Journal of Sexual and Reproductive Health, 2026)
Background: Recurrent cervical pre-cancerous lesions remain a major clinical challenge in preventing progression to invasive cancer and achieving long-term remission. Persistent infection with high-risk human papillomavirus (HPV), particularly subtype 16, is strongly associated with recurrence, especially in women under 40 years of age. Method: This narrative review analyzed recent literature focusing on the main determinants of recurrence after treatment of cervical pre-cancerous lesions, including viral, surgical, and immunological factors. Result: The findings showed that incomplete surgical excision significantly increased the risk of recurrence. The type of surgical procedure also influenced outcomes, with cold knife and laser conization associated with lower recurrence rates than LLETZ. Post-treatment HPV vaccination was found to reduce recurrence by enhancing immunity against re-infection. Implication: These findings highlight the importance of individualized treatment selection, complete lesion excision, and the use of HPV vaccination as part of a comprehensive strategy to minimize recurrence and improve long-term outcomes.Novelty: This review provides an integrated overview of viral, surgical, and immunological factors influencing cervical lesion recurrence, emphasizing the importance of combining optimal surgical technique with preventive immunization.